Design of Cassava Cutting Tool Based on Mechanical Calculation Analysis - Wilarso; Aswin Domodite (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2026)
This research focuses on the design, fabrication, and performance evaluation of a cassava and banana cutting machine prototype aimed at improving the uniformity of slice thickness and the efficiency of the chip production process. The design stages were carried out systematically using AutoCAD and SolidWorks software to produce geometric configurations and cutting mechanisms that suit the characteristics of the tuber and fruit materials. Next, the virtually validated design was realized through a fabrication process into a functional prototype. Machine performance testing was carried out using cassava test material with an average diameter of 50 mm. Each test condition was repeated five times (n = 5) to ensure data repeatability. The performance parameters analyzed included production rate (throughput) in kg/hour, slice thickness in millimeters which was statistically analyzed using the mean and standard deviation values, and electrical power consumption during machine operation. The test results showed that the machine was capable of producing an average throughput of 50 ± 3 kg/hour with a slice thickness of 2.0 ± 0.15 mm and a coefficient of variation of 7.5%, which indicates a good level of slice uniformity. Power consumption was recorded at 3.1 kW under standard operating conditions. Compared to manual cutting methods, the use of this machine reduced cutting time per kilogram of material by approximately 60%. Based on these results, it can be concluded that the developed prototype is effective in improving process efficiency and sliced ​​quality. Further research is recommended to optimize the material feed system and test the machine's performance on a wider variety of raw materials Keywords: Cutting machine; cassava; banana; slice uniformity; mechanical design